2015
DOI: 10.1589/jpts.27.1893
|View full text |Cite
|
Sign up to set email alerts
|

Association between toe grasping strength and accelerometer-determined physical activity in middle-aged and older women

Abstract: [Purpose] To test the hypothesis that toe grasping strength is associated with daily physical activity in older adults. [Subjects] Fifty-seven Japanese women, aged 52–78 years, volunteered. [Methods] Toe grasping and knee extension strength were measured. Physical activity was also measured, using an accelerometer, and the total duration of each level of exercise intensity (light, moderate, and vigorous) and average step counts were calculated. Subjects were separated into two groups on the basis of accelerome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Another possibility is that such associations are linked to the physical activity level and/or gait speed. Toe flexor strength reflects the level of physical activity [9, 12] and gait speed [5]. Physical activity intervention reduces the risk of type 2 diabetes and hypertension [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility is that such associations are linked to the physical activity level and/or gait speed. Toe flexor strength reflects the level of physical activity [9, 12] and gait speed [5]. Physical activity intervention reduces the risk of type 2 diabetes and hypertension [44].…”
Section: Discussionmentioning
confidence: 99%
“…Toe flexor strength is associated with the amount of low-to-moderate intensity physical activity [9, 12]. A previous study showed that toe flexor strength/BM in a higher daily step counts group (≥8000) was greater than that in a lower daily step counts group, however, such a difference in knee extensor strength/BM was not observed in women aged 52–78 years [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conToe flexor strength and diabetes trast, compared with the strength of lower limbs, HGS is lower or not associated with the amount of physical activity [20,39]. In addition, TFS is associated with gait speed [16,38]. Lower-limb muscle strength is a slightly better predictor of gait speed than HGS [40].…”
Section: Discussionmentioning
confidence: 99%
“…A lower amount of physical activity is a risk factor for type-2 diabetes mellitus [36], and gait speed is associated with the prevalence of diabetes mellitus [22,37]. TFS is positively related to physical activity [20,38]. In conToe flexor strength and diabetes trast, compared with the strength of lower limbs, HGS is lower or not associated with the amount of physical activity [20,39].…”
Section: Discussionmentioning
confidence: 99%